Indigenous tourism operators: the vanguard of economic recovery in the Chatham Islands. (7th July 2010) - Cardow, Andrew; Wiltshier, Peter
This paper highlights the emergent enthusiasm for tourism as a saviour for economic development in the Chatham Islands. The Chatham Islands are a remote, economically depressed region of New Zealand. Traditional income streams are in decline and tourism offers a way to redress such a decline. Tourism in the islands is based upon a mixture of indigenous fervour for the heritage and environment of the Chatham Islands and the land- and marine-based opportunities that are present. The Chatham Islands represent a case study that defines the good practices of endogenous planning and exemplifies community-based tourism. The methodology was a qualitative approach based on the refinements of grounded theory. In addition, both primary and secondary longitudinal research was used. This method allowed the construction of a case study to illustrate the role that indigenous tourism operations play in the islands' economic recovery. It was found that there was a tension between community cohesion and economic development. The research demonstrates that there is a shift in resources and power when accepted means of economic development start to fail. This article illustrates the political and economic hurdles that tourism operators in remote areas need to consider. The paper highlights how community involvement and community 'buy in' can assist policy makers and would-be entrepreneurs in similar circumstances.